Integrated Guidance and Control of Interceptor Missile Based on Asymmetric Barrier Lyapunov Function - Xiang Liu; Xiaogeng Liang (International Journal of Aerospace Engineering)
In this study, a novel integrated guidance and control (IGC) algorithm based on an IGC method and the asymmetric barrier Lyapunov function is designed; this algorithm is designed for the interceptor missile which uses a direct-force/aerodynamic-force control scheme. First, by considering the coupling between the pitch and the yaw channels of the interceptor missile, an IGC model of these channels is established, and a time-varying gain extended state observer (TVGESO) is designed to estimate unknown interferences in the model. Second, by considering the system output constraint problem, an asymmetric barrier Lyapunov function and a dynamic surface sliding-mode control method are employed to design the control law of the pitch and yaw channels to obtain the desired control moments. Finally, in light of redundancy in such actuators as aerodynamic rudders and jet devices, a dynamic control allocation algorithm is designed to assign the desired control moments to the actuators. Moreover, the results of simulations show that the IGC algorithm based on the asymmetric barrier Lyapunov function for the interceptor missile allows the outputs to meet the constraints and improves the stability of the control system of the interceptor missile.